DTM models to enhance planning of timber harvesting - Đuka Andreja; Poršinsky Tomislav; Vusić Dinko (Glasnik Šumarskog Fakulteta: Univerzitet u Beogradu, 2015)
This paper studies the applicability of DTM with the resolution of 4 × 4 m for the analysis of macro-topographic factors (terrain slope, aspect, terrain ruggedness index) and one part of micro-topographic factors (occasional and constant streams) as features important for vehicle mobility during timber skidding. The analysis of directions of timber extraction in relation to the spatial position of primary forest traffic infrastructure of the study area was conducted in order to determine from which forest areas timber will be extracted up or down the slope (moving of loaded vehicle). Determination of water bodies (streams) and the surrounding sensitive areas was carried out using GIS tool TauDEM. Unevenness of the terrain was determined based on the Terrain Ruggedness Index (TRI) which showed moderately to very rugged terrain on 60.1% of the research area where vehicle mobility could be difficult (if not impossible) i.e. the necessity of a secondary forest road network is clear. DTM analysis of study area regarding vehicle (skidder) mobility and possible planning of timber extraction indicated different availability and quality of data. Digital terrain models present a good basis for the analysis of key constraints for forestry vehicles mobility or terrain trafficability (slope and direction of timber extraction). Using DTM of higher resolution (e.g. LiDAR images), will increase the accuracy of the results and the quality of the analysis.